MRSI and DTI: a multimodal approach for improved detection of white matter abnormalities in alcohol and nicotine dependence - Wang, Jean J. (2009)
Our previous proton magnetic resonance spectroscopic imaging ((1)H MRSI) studies showed that the frontal lobe white matter (WM) in smoking recovering alcoholics (sRA) had lower concentrations of N-acetylaspartate (NAA), a marker for neuron viability, compared to both nonsmoking recovering alcoholics (nsRA) and a control group of nonsmoking light drinkers (nsLD). Using diffusion tensor imaging (DTI) in a similar population, we found lower fractional anistropy (FA), a microstructural measure of WM fiber integrity, in regions of specific fiber bundles within frontal WM of recovering alcoholics compared to light drinkers. In this study, we hypothesized that in these regions of lower FA, NAA concentrations in the alcoholic groups are lower than in non-alcoholic controls. We hypothesized further that sRA have lower regional NAA concentrations than nsRA. We retrospectively analyzed existing (1)H MRSI data by quantitating metabolite concentrations from voxels that corresponded to previously identified WM regions of lower FA, and from a control region of normal FA in alcoholics. We found significant NAA concentration differences between groups in regions of abnormal FA. In particular, sRA had significantly lower NAA concentration than nsLD, but in no region was NAA significantly lower in nsRA than nsLD. Furthermore, no NAA group differences were detected in a frontal WM region of normal FA. These results indicate regionally localized NAA loss within the frontal WM, and specifically NAA loss in regions of low FA. Compared to our previous lobar analyses, DTI-guided MRSI analysis allows the selective evaluation of small WM regions with microstructural injury, thereby increasing statistical power to detect relevant pathology and group differences. DTI-guided MRSI analyses promise to contribute to a better understanding of brain injury in alcohol and nicotine dependence and, by extension, perhaps in other neurodegenerative diseases as well.